NEDD4 triggers FOXA1 ubiquitination and promotes colon cancer progression under microRNA-340-5p suppression and ATF1 upregulation. Issue 11 (2nd November 2021) - Yue, Meng; Yun, Zhennan; Li, Shiquan; Yan, Guoqiang; Kang, Zhenhua
ABSTRACT: NEDD4 is an E3 ubiquitin ligase that recognizes substrates through protein–protein interactions and is involved in cancer development. This study aimed to elucidate the function of NEDD4 in colon cancer (CC) progression and its mechanism of action. NEDD4 was abundantly expressed in CC tissues and cells, and the overexpression of NEDD4 promoted the growth and metastasis of xenograft tumours as well as the tumorigenesis rate of primary CC in mouse models. In in vitro experiments, the silencing (or upregulation) of NEDD4 inhibited (or increased) the viability, invasion, and epithelial-to-mesenchymal transition of CC cells. The binding relationships between NEDD4 and FOXA1, FOXA1 and microRNA (miRNA)-340-5p, and miR-340-5p and ATF1 were validated by Co-immunoprecipitation, chromatin immunoprecipitation and luciferase assays, and NEDD4 was demonstrated to trigger FOXA1 ubiquitination and degradation. FOXA1 transcriptionally activated miR-340-5p, which subsequently bound to ATF1 mRNA. The upregulation of FOXA1 or miR-340-5p or the downregulation of ATF1 blocked certain functions of NEDD4 in CC cells. Altogether, NEDD4 was demonstrated to trigger FOXA1 ubiquitination and promote CC progression under the involvement of microRNA-340-5p suppression and ATF1 upregulation.